Determinant of Islamic bank Savings Customers Satisfaction: A Case of Indonesian Islamic Bank - ., Widyarini; ., Sunaryati (Journal of Ecohumanism, 2024)
Bank competition is fierce among conventional banks, Islamic banks, and among these types of banks. To win the competition, bank management must try to satisfy customers. This study aimed to determine the determinants of customer satisfaction in terms of savings. This study aimed to determine the determinants of voluntary consumer satisfaction. This research is a development of the Peng and Moghavvemi (2015) model and only using 'Voluntary Savings Customers' of Islamic banks and add three variables. There were 247 participating respondents. Respondents came from Bank Syariah Indonesia (BSI), Bank Muamalat, Bank BPD Syariah, Bank BTN Syariah, Bank Bukopin Syariah. Snowball sampling was used. The analysis tool used was Partial Least Square (PLS) with SmartPLS software. The results showed that empathy had a moderately significant effect, whereas assurance; reliability; tangibles and compliance had a significant effect on perceived value. On the other hand, the empathy and trust have a significant effect on customer satisfaction. The test results also show that assurance, reliability, perceived value, tangibles, compliance, and religiosity are not significant for Customer Satisfaction.